2011
DOI: 10.1017/s0003598x00067521
|View full text |Cite
|
Sign up to set email alerts
|

An archaeology of salt production in Fiji

Abstract: The authors report the first exposure of prehistoric salt-working in the Pacific, one that used solar evaporation of sea water on large flanged clay dishes. This short-lived industry of the seventh century AD disappeared beneath the dunes, but its documented nineteenth-and twentieth-century successors offer it many useful analogies: the salt, now extracted by boiling brine, was supplied to inland communities upriver, where it functioned as a prime commodity for prestige and trade and an agent of social change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Rather, technological change occurs in ceramic temper materials, in the forming methods by which jars are produced, in the loss or addition of vessel forms, and in ceramic firing technology. Similarly, change in respective burial practices appears to have occurred in parallel fashion, while site function is dramatically varied between the two occupations (Burley 2005;Burley et al 2011). The cumulative extent of these changes, we believe, represents a significant disjuncture in the archaeological record at Sigatoka, one where an intrusive and different population came to reside at the mouth of the Sigatoka River.…”
Section: Implications and Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Rather, technological change occurs in ceramic temper materials, in the forming methods by which jars are produced, in the loss or addition of vessel forms, and in ceramic firing technology. Similarly, change in respective burial practices appears to have occurred in parallel fashion, while site function is dramatically varied between the two occupations (Burley 2005;Burley et al 2011). The cumulative extent of these changes, we believe, represents a significant disjuncture in the archaeological record at Sigatoka, one where an intrusive and different population came to reside at the mouth of the Sigatoka River.…”
Section: Implications and Discussionmentioning
confidence: 81%
“…Navatu phase people took up residence on top of the former village after that event, this group having a distinct and different type of ceramic assemblage. The economic rationale for this occupation was the production of sea salt using large ceramic salt trays for solar evaporation of seawater (Burley et al 2011). Presumably in the onslaught of blowing sand, this village also was abandoned and subsequently buried.…”
Section: V Burley and K Edinboroughmentioning
confidence: 99%
“…While some authors have identified the transition from Fiji Plainware to Navatu around 1800 years ago using data from various sites across the Fiji Islands [68][69][70], this transition appears to occur later at Sigatoka, during the process of formation of Level 2 [59]. Excavations at the easternmost end of the dune revealed two stratigraphically separate but superimposed domestic occupations corresponding to the Fijian Plainware and Navatu phases respectively, with a village occupation dated to 1,433-1,298 cal BP and a subsequent occupation focused on sea salt production dated to1,330-1,266 cal BP [59,[71][72][73]. The change from Fijian Plainware to Navatu is seen as an abrupt cultural modification, interpreted by some as indicating interactions with external population(s) (e.g.…”
Section: Sigatoka Sand Dunes Archaeological Context and Chronology Is...mentioning
confidence: 99%
“…The pots in question function as containers for boiling brine in stoves, as well as standard units of measurement for trade, something we see in Mesoamerica and many other areas of the world, including the island of Fiji (Melanesia, South Pacific Ocean). In Fiji, clay pots were used in the process of salt elaboration, though the technology employed there relied on solar evaporation rather than boiling brine over fire (Burley et al 2011), as occurred in the Philippines. The assemblage here consists of decorated jars, probably used for water (or brine) transport in the saltworks, and a type of shallow vessel called a “salt tray,” used for the solar evaporation of brine.…”
Section: The Salt-making Tool Assemblagementioning
confidence: 99%